Adubação Combinada de N e P no Solo no Crescimento e Nutrição de Cafeeiro Conilon - Barros, Vanessa Maria de Souza (2018)
With the development of new clones of conilon coffee, many studies have been carried out to evaluate the effect of isolated levels of N, P and K. However, soil nutrient combination studies are necessary to verify the interaction between them and